TINJAUAN HUKUM SANKSI PIDANA PADA PELAKU PENYEBARAN KONTEN PORNOGRAFI DI INTERNET - Rengga Fatma Jaya; Noenik Soekorini; Sri Astutik; Vieta Imelda Cornelis (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstrak. The development of the times is so rapid, the mode of spreading pornographic content has also spread through the internet. The formulation of the crime of pornography is also regulated in article 27 paragraph (1) of Law Number 11 of 2008 concerning Electronic Information and Transactions, which reads: